Protection Of Human Rights In The Indonesian Constitution: An Analysis Of The 1945 Constitution - Rahman, Abdul; Sugianto; Hidayat, Dudung (Jurnal Legisci, 2024)
This paper analyzes the protection of human rights (HAM) in the 1945 Constitution of the Republic of Indonesia (1945 Constitution). The research uses normative juridical methods with conceptual and legislative approaches to examine how the 1945 Constitution protects human rights. The study results show that the 1945 Constitution has comprehensively accommodated the protection of human rights, especially after a series of amendments. This amendment has strengthened the guarantee of human rights protection and clarified the basic rights guaranteed by the Constitution. However, even though human rights protection has been accommodated in the 1945 Constitution, implementing these protections still faces various challenges in practice. Some of the main challenges identified include inconsistencies in law enforcement, lack of harmonization of laws and regulations, and low public awareness and understanding of their rights. This paper concludes that further efforts are needed to strengthen human rights enforcement in Indonesia. These efforts include harmonization of relevant laws and regulations, capacity building of law enforcement institutions, and campaigns to raise public awareness of the importance of human rights. Thus, to achieve adequate human rights protection in Indonesia, collaboration between the government, legal institutions, and the wider community is needed to create an environment conducive to respecting and enforcing human rights.